Enhancing children's role as agents of change in the utilization of household medicinal plants - Wijaya, Dian Rezki; Zhahiirah, Andi Nur Shabaa; Lestari, Sri Ayu; Nurhasnina, Sitti; Syarif, Alwiyah Nur; Saleh, Syamsudhuha (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
The utilization of household medicinal plants (in Indonesia known as TOGA) as a form of local wisdom holds great potential for improving public health. However, its use as an alternative traditional treatment remains suboptimal, especially among the younger generation. TOGA not only serves as cooking ingredients but also offers natural and independent health benefits. Therefore, this empowerment activity aims to enhance students' knowledge and awareness of the benefits of TOGA through educational counseling and practical garden-making activities. The program was conducted on October 13-14, 2024, at SD Negeri 21 Rumbia, involving 52 students from grades 3, 4, and 6. The methods used included lectures, leaflet distribution, an interactive game called "Guess the Picture", Q&A sessions, and hands-on planting of six types of TOGA plants: ginger, lemongrass, galangal, turmeric, basil, and celery. The evaluation was carried out using pre-tests and post-tests with five questions designed to measure students' knowledge improvement. The results showed a significant increase (p < 0.05) in students' knowledge, with the percentage of those classified as having sufficient knowledge rising from 11.5% to 26.9%. In addition to enhancing knowledge, the hands-on TOGA planting activity provided students with practical experience that reinforced their understanding of the health benefits of medicinal plants. With active student involvement and support from the school, this program is expected to contribute to public health improvement through the sustainable use of TOGA.